Migration crisis fueled by the challenges and uncertainties facing the new Afghanistan - Tok, Ufuk (Cappadocia Journal of Area Studies, 2023)
After the US withdrew from Afghanistan by ending its 20-year occupation, the country was completely under the administration of the Taliban. However, at the end of this process, some uncertainties emerged such as what the political administration, social life and economic situation would be in Afghanistan, as well as how security and justice would be established. The Interim Government, formed by the Taliban, had to meet the expectations in the international arena while overcoming these uncertainties. However, it has also been understood that the integration of Afghanistan under the Taliban administration with the contemporary world will not be rapid. In addition, irregular migration to the West due to the long-lasting war in Afghanistan, and the effect of these increasing mass movements over time, the new uncertainties that emerged in Afghanistan, on irregular migration were also analyzed. Thus, it has been tried to determine whether irregular migration originating from Afghanistan can be prevented.